2013
DOI: 10.1186/1869-5760-3-49
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic ophthalmia: to the twenty-first century and beyond

Abstract: Sympathetic ophthalmia is a rare bilateral granulomatous inflammation that follows accidental or surgical insult to the uvea of one eye. Onset of sympathetic ophthalmia can be insidious or acute, with recurrent periods of exacerbation. Clinical presentation shows mutton-fat keratic precipitates, choroidal infiltrations, and Dalen-Fuchs nodules. Histopathology reveals diffuse or nodular granulomatous inflammation of the uvea. Prevention and treatment strategies for sympathetic ophthalmia are currently limited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
113
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 62 publications
0
113
0
6
Order By: Relevance
“…Sympathetic cochleolabyrinthitis represents a explanation considering the time of onset, 80% between the first two weeks and three months and 10% in the following year in the sympathetic ophthalmia [11], the loss of all frequencies, the association with vertigo and the good response of one of our patient to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sympathetic cochleolabyrinthitis represents a explanation considering the time of onset, 80% between the first two weeks and three months and 10% in the following year in the sympathetic ophthalmia [11], the loss of all frequencies, the association with vertigo and the good response of one of our patient to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical injury could result in a release of sequestered antigens to the systemic circulation, which would be capable of damaging to the contralateral ear, what has been named in ophthalmology as sympathetic ophthalmia, in which an immunologic response following eye trauma or surgery injuries the contralateral eye [10,11]. This has been studied in animal models in which sensitized lymphocytes were able to transfer autoimmune inner disease, resulting in cellular infiltration by neutrophil granulocytes and lymphocytes in the scala tympani, loss of outer hair cells in the apical turn and loss of detection of TEOAE in the studied animals [12].…”
Section: Discussionmentioning
confidence: 99%
“…The fellow non-traumatized sympathizing eye also shows similar inflammatory response usually with mutton-fat KPs suggesting involvement of autoimmune response [1]. Though the time from ocular injury to onset of SO was said to vary greatly, ranging from a few days to fifty years with 90% of the cases occurring within 1 year [2][3][4][5], recent series showed that only one-third of patients developed SO within 3 months and fewer than 50% did so within 1 year of injury [6].…”
Section: Introductionmentioning
confidence: 94%
“…In our patient, the injury had occurred to the right eye nearly 20 years ago. SO is a serious public health problem as it can lead to blindness in both eyes [2][3][4].…”
Section: Discussionmentioning
confidence: 99%